Analisis Penanganan Sayuran pada Proses Persiapan Hidangan Buffet di Hotel Mercure Surabaya Grand Mirama - Allicia Avilla; Lilis Sulandari; Niken Purwidiani; Lucia Tri Pangesthi (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
Vegetables are a type of food that comes from plants that are easily perishable because of their high water content so they require handling according to their type to extend their shelf life. The purpose of this study is to determine the handling of vegetables in the preparation process of buffet dishes at the Hotel. This study uses a qualitative descriptive approach. The data collection techniques used are interviews, observations, and document studies. The data analysis technique used is qualitative descriptive analysis. The results of this study include the importance of handling vegetables to keep vegetables of good quality and fresh, vegetables become attractive when served and arranged for buffet dishes, and vegetables are more guaranteed and more durable when stored. Vegetable handling starts from selection, weeding, washing, cutting, blanching, pre-cooling, to vegetable storage. Kitchen Hotel Mercure has carried out almost all stages in accordance with standard operating procedures so that it can meet the needs of vegetables according to the type of cuisine and the quality of vegetables and minimize losses.